Lean Practices Pertaining Hard and Soft Factors in Service Sectors - Sorooshian, Shahryar; Siti Aissah, Mad Ali (Romanian Society for Quality Assurance - SRAC, 2017)
Many of Lean manufacturing tools and practices are being implemented in the different sectors with and without being realized nowadays. This research objective is double folded. Employing 10 predictor variables, the relationship and impact of Lean practices on Lean performance was identified. The second objective was conducted to identity the significance disparity in the impact of soft and hard factors; whether to give priority to either one or equal priority. A lean performance model was built with soft predictor variables comprising of quality leadership, group problem solving, training, worker empowerment and multi-skilling developing and hard predictor variables comprising of standardized operations, 5S, reorder point, supplier development and continuous flow. Although this study failed to find enough support for some of the factors, a few factors find enough evidence to be part of lean performance predictors.